A A STUDY ON KNOWLEDGE, ATTITUDE, AND PRACTICE OF PHARMACOVIGILANCE TOWARD ADR REPORTING AMONG JUNIOR RESIDENT, SENIOR RESIDENT, AND CONSULTANT DOCTORS IN TERTIARY CARE SETTING OF TEACHING MEDICAL INSTITUTION - NATH SOM; SHARMA DEEPAK; NATH MANJUSHA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of this study was to improve the adverse drug reaction (ADR) reporting rate. This study was undertaken to evaluate the knowledge, attitudes, and practices of the health-care professionals at a tertiary care teaching hospital, regarding ADR monitoring and pharmacovigilance (PV). Methods: This cross-sectional study was conducted in a tertiary health-care setting of the State Medical College of Uttar Pradesh, health professionals, such as Junior Residents (JRs), Senior Residents (SRs), and consultants were participated in the study. Knowledge, attitudes, the voluntary reporting system, procedures related and reasons for non-reporting of ADRs, etc., with respect to PV was assessed. Informative data were collected and analyzed by applying appropriate software. Results: Most of the study participants (62.4%) felt that pharmacovigilance report should be made mandatory. The majority of JR knew the theoretical definition and purpose of PVs comparatively more than SR and consultants. Responses showing the attitude of the study participants toward PVs depict that most of the participants (62.4%) felt that PVs report should be made mandatory. Practical aspects of ADRs by different cadres of participant, namely, consultants (68.0%), SR (50%), and JR (35.7%) were found to be statistically significant; p=0.037. The factors discouraging health professionals from reporting ADRs are mainly 1) non-remuneration, 2) difficulty in taking decision, whether ADR has occurred or not or 3 think that single case will not affect ADR database, or 4) lack of time. Conclusion: Only few of the health professional (20%) were ever reported an ADR but still there is great need to create awareness among the junior/ senior doctors/consultants to improve the reporting of ADRs. An educational intervention and improvement of facilities in coordinating with health-care professionals would definitely bring on a difference in ADRs.